Affective Immersion in Large-Scale Moving Image Installations - Zsolt Gyenge (Acta Universitatis Sapientiae: Film and Media Studies)
The post-cinematic moving image installations enabled by high-definition projection technologies create such atmospheric environments for their visitors that generate new forms of spectatorship activating both self-reflexive awareness of mediation and affective response to the surrounding audio-visual spectacle. The article intends to provide a description of this viewer experience by developing two concepts (embodied self-reflexivity and affective immersion) apprehending the spectacle of the exhibited moving image. To this end, phenomenological theories of affectivity will be briefly explored alongside the invocation of Deleuze’s term affection-image and Giuliana Bruno’s idea of atmospheric projection. The final suggestion of the paper is that the spectators’ experience of such moving image installations is best understood through the description of the interplay between what I term embodied self-reflexivity and affective immersion.